Structural imperialism and the pandemic of untreated pain in the Asia region - Katherine Pettus (Journal of Illicit Economies and Development (JIED), 2023)
This paper takes a transdisciplinary genealogical approach to the current global lack availability of internationally controlled essential medicines in more than 80% of the world, with a particular focus on the Asia region. More than six decades after the Single Convention on Narcotic Drugs (SC), whose Parties were "concerned with the health and welfare of mankind," had stipulated that these substancs are "indispensable" for the relief of pain and suffering, experts report that while the global consumption of opioids has increased, the consumption in most Asian countries has not increased at the same rate and that access is significantly impaired by widespread over-regulation that continues to be pervasive across the region. The tragic irony of this situation is that traditional opium-based medicines used for millennia in the region are unavailable, inaccessible, and unaffordable in these erstwhile imperial peripheries where their botanical sources are plentiful but forbidden, while global pharmaceutical corporations peddle their expensive synthetic opioids - formulated in the metropolis - to formerly colonized populations who cannot afford them and whose health workers are largely untrained to prescribe them.
Keywords: 330; Internationally controlled essential medicines; Single Convention on Narcotic Drugs; opium; empire; decolonizing; palliative care; empire